Effects of environmentally relevant concentrations of microplastics on amphipods - Rani-Borges, Bárbara [UNESP]; Meitern, Richard; Teesalu, Paul; Raudna-Kristoffersen, Merilin; Kreitsberg, Randel; Heinlaan, Margit; Tuvikene, Arvo; Ivask, Angela (Elsevier, 2022)
Lack of microplastics (MP) toxicity studies involving environmentally relevant concentrations and exposure times is concerning. Here we analyzed the potential adverse effects of low density polyethylene (LDPE) MP at environmentally relevant concentration in sub-chronic exposure to two amphipods Gmelinoides fasciatus and Gammarus lacustris, species that naturally compete with each other for their habitats. 14-day exposure to 2 μg/L (8 particles/L corresponding to low exposure) and 2 mg/L (∼8400 particles/L, corresponding to high exposure) of 53–100 μm LDPE MP were used to assess ingestion and egestion of MP, evaluate its effects on amphipod mortality, swimming ability and oxidative stress level. Both amphipod species were effectively ingesting and egesting LDPE MP. On the average, 0.8 and 2.5 MP particles were identified in the intestines of each amphipod exposed to 2 μg/L and 2 mg/L LDPE MP, respectively. Therefore, intestinal MP after 14-day exposure did not fully reflect the differences in LDPE MP exposure concentrations. Increased mortality of both amphipods was observed at 2 mg/L LDPE MP and in case of G. lacustris also at 2 μg/L exposure. The effect of LDPE on swimming activity was observed only in case of G. fasciatus. Oxidative stress marker enzymes SOD, GPx and reduced glutathione GSH varied according to amphipod species and LDPE MP concentration. In general G. lacustris was more sensitive towards LDPE MP induced oxidative stress. Overall, the results suggested that in MP polluted environments, G. lacustris may lose its already naturally low competitiveness and become overcompeted by other more resistant species. The fact that in the sub-chronic foodborne exposure to environmentally relevant and higher LDPE MP concentrations all the observed toxicological endpoints were affected refers to the potential of MP to affect and disrupt aquatic communities in the longer perspective.
Keywords: Crustaceans; Gammarus fasciatus; Gmelinoides lacustris; LDPE; Paraquat; SiO2